2000
DOI: 10.1111/j.1365-2672.2000.tb05341.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the detection and isolation of Shiga toxin-producingEscherichia coli

Abstract: SUMMARY Shiga toxin‐producing Escherichia coli (STEC) are an important cause of haemorrhagic colitis and the diarrhoea‐associated form of the haemolytic uraemic syndrome. Of the numerous serotypes of E. coli that have been shown to produce Shiga toxin (Stx), E. coli O157:H7 and E. coli O157:NM (non‐motile) are most frequently implicated in human disease. Early recognition of STEC infections is critical for effective treatment of patients. Furthermore, rapid microbiological diagnosis of individual patients enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
61
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 68 publications
6
61
0
1
Order By: Relevance
“…Many studies determined the prevalence of E. coli O157:H7 on cattle carcasses which were from 0.0% to 27.8% [13,14,15]. The prevalence of E. coli O157:H7 (2.65%) isolated from carcass in this study was in close agreement with the reported prevalence of 2.9% and 3.2% in the United Kingdom [16,17], respectively. 2% in Canada [18] and five isolates (2.8%) out of 180 meat and meat products examined in South Africa [19].…”
Section: Discussionsupporting
confidence: 81%
“…Many studies determined the prevalence of E. coli O157:H7 on cattle carcasses which were from 0.0% to 27.8% [13,14,15]. The prevalence of E. coli O157:H7 (2.65%) isolated from carcass in this study was in close agreement with the reported prevalence of 2.9% and 3.2% in the United Kingdom [16,17], respectively. 2% in Canada [18] and five isolates (2.8%) out of 180 meat and meat products examined in South Africa [19].…”
Section: Discussionsupporting
confidence: 81%
“…Vertical transmission of E. coli O157:H7 from cattle feces through soil has also been demonstrated (10), and this finding highlights a possible transmission route leading to the contamination of private drinking water. All of these studies, however, have utilized culture-based methods, which rely on disruption of cells from environmental material followed by plating on selective media, such as cefixime-and potassium tellurite-containing sorbitol MacConkey agar (6). These approaches will, however, fail to target E. coli O157:H7 populations that may be in a viable but nonculturable state.…”
mentioning
confidence: 99%
“…In contrast, isolation of E. coli O157:H7 from water and other environmental samples is laborious. Culture is problematic due to large numbers of other flora that either overgrow or mimic the non-sorbitol-fermenting E. coli O157:H7 (12). Recently, immunomagnetic separation (IMS) has helped improve recovery by providing an antibody-based concentration procedure that uses magnetic beads coated with antibody against E. coli O157.…”
mentioning
confidence: 99%